Antimicrobial cellulose hydrogels against gram-positive and gram-negative bacteria - Miño, Karla; Pérez, Antonela; Iza-García, Tamia Xaymara; Cabascango, Dayanna Gabriela; Gordillo, Catalina; Gordillo, Andrea; Vispo, Nelson; Machado, António; Zamora-Ledezma, Camilo; Alexis, Frank (Frontiers in Soft Matter, 2024)
The development of hydrogels has a significant impact in fields such as tissue engineering and biomedical devices. The present study tests different cellulose particles extracted from plants to produce hydrogels and identify if these particles and hydrogels have antimicrobial properties. Nine cellulose particles from Ecuadoran biodiversity were obtained using an established chemical extraction protocol, characterized using known techniques, and evaluated for bacterial growth in-vitro. In addition, two particles of nine were selected to perform bacterial growth rates and bacterial adhesion assays. The bacterial growth rates with cellulose F1 and F53 were similar to the positive control (with antibiotic) with both Escherichia coli ATCC 25922 and TG1 strains. However, the results showed that the bacterial growth rate with seven of the nine cellulose particles was lower than the negative control (without antibiotics) suggesting antifouling properties. Based on the results using cellulose particles and hydrogels with antifouling properties, we prepared a plant extract to test the bactericide properties against Gram-positive (Staphylococcus aureus ATCC 25923) and Gram-negative (E. coli ATCC 25922) bacteria, evidencing the highest inhibitory effect at 40 and 60 mg/mL against S. aureus and E. coli, respectively. Lastly, we encapsulated the bactericide plant extract into the anti-fouling hydrogel. The results demonstrated that the combination of antifouling and bactericide properties could be an alternative approach for surface-modified cellulosic materials applications in the future.